KERAGAMAN TANAMAN DAN SUMBANGAN PENERIMAAN TUMPANGSARI KOPI DAN LADA DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Fembriarti Erry Prasmatiwi; Rusdi Evizal; Otik Nawansih; Novi Rosanti; Rommy Qurniati; Purba Sanjaya (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2023)
In Tanggamus, pepper trees are commonly intercropped in coffee plantations with coffee-pepper intercropping type (dominant coffee), coffee pepper type (dominant pepper), and agroforestry type. The intercropping system plays a role in improving agro-ecosystems, increasing farm productivity and income. This study aimed to study crops diversity, productivity and income of coffee-pepper intercropping farming. This study used a survey method. The survey locations were determined purposively in two sub-districts which were centers of coffee cultivation in Tanggamus, namely Ulu Belu and Air Naningan District. In the Ulu Belu District, the villages of Sinar Banten, Sinar Galih, Petai Kayu were selected purposively, and in the Air Naningan District were Datar Lebuay Village and Air Kubang Village. Primary data was collected by visiting plantations and interviewing farmers. Sample farmers were determined randomly with a total of 137 samples. The diversity of intercrops was analyzed by calculating the Benefit Index Value and Importance Value Index. The results showed that coffee plantations were generally intercropped (79-86%) with coffee and pepper. Based on the Importance Value Index, in Ulu Belu the most important intercrops were pepper, banana, avocado and cayenne pepper, while in Air Naningan they were pepper, jengkol, cayenne pepper and durian. The income of intercropping coffee farmers could reach IDR 24 million/hectare/year. This income was obtained from both the coffee-pepper intercropping or the coffee-non-pepper intercropping. The productivity of intercropping coffee ranged from 528-1,097 kg/hectare. The productivity of pepper intercrops ranged from 0.45-0.54 kg per tree and contributed 11-29% of coffee income.